2015
DOI: 10.1063/1.4936899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isotropic and anisotropic slip on droplet impingement on a superhydrophobic surface

Abstract: The dynamics of single droplet impingement on micro-textured superhydrophobic surfaces with isotropic and anisotropic slip are investigated. While several analytical models exist to predict droplet impact on superhydrophobic surfaces, no previous model has rigorously considered the effect of the shear-free region above the gas cavities resulting in an apparent slip that is inherent for many of these surfaces. This paper presents a model that accounts for slip during spreading and recoiling. A broad range of We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The contact time on the SHS was 11.5 ms. At the same speed, the impact on the micro-aniso-SHS was similar to that on the SHS, but the rim exhibited undulations during the spreading stage (Supplementary Figure S2c), in agreement with previous reports. 25,26 The maximum spreading factors (the ratio of the maximum spreading diameter to the initial diameter of the drop) along the x and y directions were 2.59 and 2.47, respectively (Supplementary Figure S2f and g). Therefore, the spreading shape was oblong and the momentum was slightly greater along the x direction than the y direction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contact time on the SHS was 11.5 ms. At the same speed, the impact on the micro-aniso-SHS was similar to that on the SHS, but the rim exhibited undulations during the spreading stage (Supplementary Figure S2c), in agreement with previous reports. 25,26 The maximum spreading factors (the ratio of the maximum spreading diameter to the initial diameter of the drop) along the x and y directions were 2.59 and 2.47, respectively (Supplementary Figure S2f and g). Therefore, the spreading shape was oblong and the momentum was slightly greater along the x direction than the y direction.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobic silica nanoparticle decoration is shown in Figure 1c, which rendered both the stripes and the grooves water-repellent. The prepared surface had three levels (macro/micro/nano) structures and the biggest difference between the layers and those in conventional anisotropic SHSs [24][25][26][27] was the presence of the macrotextured parallel stripes. Therefore, this surface is defined as a macro-aniso-SHS in the present article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the bottom of the droplet houses the largest velocity gradients [41], the reduction of liquid viscosity (due to increased temperature) is significant and allows for larger spreading. Second, Leidenfrost spreading encounters virtually no solid-liquid contact and thus approaches an infinite slip scenario [42], which is in contrast with spreading on the SHB surface at room temperature, which experiences no shear over cavities but frictional resistance over the pillars.…”
Section: Maximum Spread Diametersmentioning
confidence: 99%
“…Grishaev et al [276] studied the effect of adding particles on impact of water droplets on hydrophilic and hydrophobic surfaces and observed that the particles make splashing occur earlier. Clavijo et al [277] also investigated the impact on superhydrophobic surfaces considering the effects of slip (both isotropic and anisotropic) and observed that the slip can significantly affect the impact behavior at high We numbers, but its effects can be neglected at low We numbers. Wu et al [278] numerically simulated the impact of droplets on solid surface using Lattice Boltzmann method.…”
Section: Recent Studiesmentioning
confidence: 99%